Penguatan Pemahaman Ilmu Tajwid: Upaya Meningkatkan Kualitas Membaca Al-Qur’an Santri Pondok Pesantren Ajmalul Huda Kampung Rimba Sawang - Reynaldi, Reynaldi Aulia Rahim; Syamsuar, Syamsuar; Hanif, Hanif; Taran, Jovial Pally; Kasih, Dar; Mukhlizar, Mukhlizar; Hasan, Khairuddin (MEUSEURAYA - Jurnal Pengabdian Masyarakat, 2024)
Strengthening the understanding of Tajweed is crucial for improving the quality of Qur'anic recitation. It is one of the fundamental aspects for anyone who wishes to beautify their recitation, correct their pronunciation, and articulate the Qur'an according to the rights of its letters. In this context, the learning process of the Qur'an at Ajmalul Huda Islamic boarding school in Rimba Sawang village is conducted using traditional methods and Talaqqi. However, the mastery of Tajweed is still not optimal. This is what motivated us, as students of the Melayu Serumpun Community Service Program (KKN) group 3 Rimba Sawang 1, to provide assistance. This assistance is a form of Community Service Program where we provide services and assistance to a community, namely the students of Ajmalul Huda Islamic boarding school in Rimba Sawang village, Tenggulun sub-district, Aceh Tamiang district, in order to improve the students' mastery of Tajweed so that the quality of their Qur'anic recitation becomes better. After the mentoring process was carried out, there was an improvement in the mastery of Tajweed among the mentees. This will certainly have an impact on their quality in reciting the Qur'an